Analyzing High Efficiency Asynchronous Motors Using Scalar Control Technique - AKÜNER, MUSTAFA CANER; TERZİ, ÜMİT KEMALETTİN (My University, 2018)
In industry, more than half of the total electrical energy produced in developed countries is converted into mechanical energy by electric motors. The usage rate of asynchronous motors is estimated to be 90% of all electric motors. For these motors, an improvement in efficiency may result in huge savings. These electric motors which have minimized losses can be improved with speed control drives to be more efficient in terms of energy consumption and performance. In speed control drives of asynchronous motors widely used in industry; scalar, vector control and direct torque control are used.In this study, in a Matlab/Simulink environment, high efficiency and standard asynchronous motors with the same characteristics were driven with scalar control technique and the simulations were compared in detail. From the point of view of both speed control performance and energy saving, it observed that high efficiency motors have more advantages.
Keywords: Bilgisayar Bilimleri, Yapay Zeka; Bilgisayar Bilimleri, Sibernitik; Bilgisayar Bilimleri, Donanım ve Mimari; Bilgisayar Bilimleri, Bilgi Sistemleri; Bilgisayar Bilimleri, Yazılım Mühendisliği; Bilgisayar Bilimleri, Teori ve Metotlar; Mühendislik, Biyotıp; Mühendislik, Elektrik ve Elektronik; Yeşil, Sürdürülebilir Bilim ve Teknoloji; Telekomünikasyon